Breaking silence: “encouraging dialogues and open discussions on human rights violations and gender based violence through Djumbais” - Jehan, Talat; Gomes, Caterina; Fawzia, Shahid; Termizi, Mazbah; Jaafar Sidek, Mohd Farid; Ahmed, Wahab (PiCCWED20, 2025)
This study examines the pervasive issues of gender-based violence (GBV) and human rights violations with a focus on the Buba and Gabu regions. Despite existing legal frameworks, GBV remains a critical concern, with women disproportionately affected by domestic violence, sexual harassment and early marriage. The study employs a mixed-methods approach, utilizing community dialogues known as "Djumbais" to explore local perceptions, identify root causes, and propose actionable recommendations. Key findings reveal that 73% of respondents perceive GBV as "Very Common" or "Common," with gender inequality, cultural norms, and lack of education cited as primary drivers. The study also highlights the ineffectiveness of the justice system, with slow legal processes and case attrition further exacerbating the issue. Community perceptions indicate a strong need for improved legal enforcement, public awareness campaigns, and economic empowerment for women. The data show that 91.2% of respondents believe enhancing intercommunity dialogue is crucial for strengthening human rights and reducing GBV. However, barriers such as ethnic and linguistic divisions, political instability, and economic inequality hinder progress. The study underscores the importance of education and awareness in empowering individuals and shifting societal norms, with 64% of respondents familiar with the Human Rights-Based Approach (HRBA). Recommendations include strengthening legal frameworks, expanding support services for survivors, and fostering community-driven initiatives to promote gender equality. The study calls for increased investment in education, particularly for women, and the establishment of inclusive community spaces to facilitate dialogue and collaboration. These findings contribute to the broader discourse on human rights and GBV in post-conflict societies, offering a roadmap for policymakers, NGOs, and community leaders to address these pressing issues effectively.